Opening pousada da Serra da Estrela in Covilhã: a two-way impact analysis - interacting with private agents - Cristina, Patrícia Alexandra de Brito (2014)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics